Flowering Period of 22 Species of Wild Begonias in Bali Botanic Garden - HARTUTININGSIH M. SIREGAR; I MADE ARDAKA; MUSTAID SIREGAR (Society for Indonesian Biodiversity, 2007)
Bali Botanic Garden has becoming one of the botanic gardens in the world that has quite complete Begonias collection. Up to now (Sept 2007) its Begonias collection consists of 215 species, comprise of 70 species of wild Begonias (originated in Indonesia) and 145 species of exotic Begonias. Some aspects of research has been done and one of them is the reproductive biology. This research is aimed to gather information about Begonia’s life cycle and also to know about the natural obstacle that cause the wild Begonias failure in forming their seeds. Final result of this research is the important informations that are useful for breeding and seed’s banking. Flowering observation were done everyday towards the 22 species of wild Begonias that are planted in Bali Botanic Garden during 2006. Data collection were done qualitatively by counting the amount of flowers that appeared. Results showed that flowering period of 22 species wild Begonias canbe grouped as : Flowering troughout the year group; Seasonal Floweing group; Rare Flowering group; Not Flowering or has not flowering Begonias group; Not all Begonias that floweing are capable to form fruits and seeds© 2007 Jurusan Biologi FMIPA UNS SurakartaKey words: Flowering Period, Begonia, Bali Botanic Garden